2022
DOI: 10.36783/18069657rbcs20210127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meloidogyne incognita on the fungal community in tobacco rhizosphere

Abstract: The often widespread and serious Root-Knot Nematode (RKN) disease is an important soil-borne disease affecting tobacco production. This study aimed to understand micro-ecological changes caused by RKN disease and interactions between disease and rhizosphere soil fungal communities. The 18S rRNA gene sequencing was used to study changes in rhizosphere fungal community of tobacco plants having RKN disease. In June 2018, a paired comparison was performed between rhizosphere fungal community structures of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Our results indicate that in infected A. konjac plants, the relative abundance of Fusarium in the rhizosphere was higher than that in healthy plants, but the abundance in infected A. muelleri was significantly lower than that in healthy plants. Penicillium can participate in the decomposition of organic matter, promote the cycles of C, N, P, and other elements, and can degrade a variety of environmentally harmful substances (Xiaolong et al, 2022). The relative abundance of Penicillium was lower in infected A. konjac than in healthy plants but higher in infected A. muelleri plants than in healthy plants.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Our results indicate that in infected A. konjac plants, the relative abundance of Fusarium in the rhizosphere was higher than that in healthy plants, but the abundance in infected A. muelleri was significantly lower than that in healthy plants. Penicillium can participate in the decomposition of organic matter, promote the cycles of C, N, P, and other elements, and can degrade a variety of environmentally harmful substances (Xiaolong et al, 2022). The relative abundance of Penicillium was lower in infected A. konjac than in healthy plants but higher in infected A. muelleri plants than in healthy plants.…”
Section: Discussionmentioning
confidence: 98%
“…Fungal diversity was analyzed using the universal primers TS1 F (5′-ACTTGGTCATTTAGAG-GAAGTAA-3′) and ITS2 R (5′-BGCTGCGTTCTTCATC-GATGC-3′). The polymerase chain reaction (PCR) amplification procedure was described by Xiaolong et al (2022) and Zheng et al (2022). The PCR product was recovered using a 2% agarose gel, further purified using the AxyPrep DNA Gel Extraction Kit (Axygen, Union City, CA, USA) according to the manufacturer's instructions, and sent to Shanghai Majorbio Bio-pharm Technology Co., Ltd. (Shanghai, China) for sequencing on the Illumina MiSeq PE300 platform (Illumina, San Diego, CA, USA).…”
Section: Pathogen Inoculation and Soil Sample Collection Healthymentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the enrichment of NP root exudates in amino acids, carbohydrates, and sucrose probably favored microorganisms capable of converting urea or other nitrogenous compounds into 1,5-dinitrobiuret. This hypothesis is plausible, since several plant-parasitic nematodes are known to cause changes in root exudates and shifts in the rhizosphere's microbial community (Wang and Bergeson, 1974;Wang et al, 1975;van Gundy et al, 1977;Yeates et al, 1998Yeates et al, , 1999Denton et al 1999;Tu et al, 2003;Dromph et al, 2006;Hasse et al, 2007;Wurst et al 2009;Tian et al, 2015;Lamelas et al, 2020;Xiaolong et al, 2022). Some soil bacteria use the enzyme biuret hydrolase to decompose biuret (Cameron et al, 2011;Aukema et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Parasitism by M. incognita led to an increase of sugars and electrolytes in tomato root exudates (Wang and Bergeson, 1974;Wang et al, 1975). Several other nematodes have also been found to cause "leaking" of carbon-and nitrogen-rich compounds, resulting in changes in the rhizosphere's microbial community (Yeates et al, 1998(Yeates et al, , 1999Denton et al 1999;Tu et al, 2003;Dromph et al, 2006;Hasse et al, 2007;Wurst et al 2009;Tian et al, 2015;Lamelas et al, 2020;Xiaolong et al, 2022). Khan (1993) and Evans and Haydock (1993) suggested that changes in root exudates could be involved in synergistic interactions involving nematodes and soilborne fungi.…”
mentioning
confidence: 99%